2019
DOI: 10.1186/s12969-019-0320-y
|View full text |Cite
|
Sign up to set email alerts
|

Patient-proxy agreement on health-related quality of life in juvenile fibromyalgia syndrome

Abstract: Background Health-related quality of life (HRQoL) measures serve as important indicators of pain-related physical and psychosocial function in youth with juvenile fibromyalgia syndrome (JFMS). While the administration of parent-proxy reported HRQoL measures in the assessment of JFMS is common, its added clinical value to patient self-reports is unclear. We aimed to determine the level of agreement on HRQoL among patients with JFMS as well as their parent-proxies and to determine factors associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Other than these items, patients and caregivers were well aligned. Combined with literature findings, these results could indicate that patient/caregiver concordance is better for some diseases (such as AD and juvenile fibromyalgia syndrome) than others (asthma) [15,16,18,19], or that concordance varies on the basis of other patient-, caregiver-, or study-related factors. Nonetheless, these results show the benefit of asking pediatric patients directly about their QoL rather than relying on a caregiver report of their child's/adolescent's QoL.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Other than these items, patients and caregivers were well aligned. Combined with literature findings, these results could indicate that patient/caregiver concordance is better for some diseases (such as AD and juvenile fibromyalgia syndrome) than others (asthma) [15,16,18,19], or that concordance varies on the basis of other patient-, caregiver-, or study-related factors. Nonetheless, these results show the benefit of asking pediatric patients directly about their QoL rather than relying on a caregiver report of their child's/adolescent's QoL.…”
Section: Discussionsupporting
confidence: 66%
“…Children’s perceptions of their own QoL may change as they mature and may also differ from their parents’ perceptions of the impact of AD on their child. To our knowledge, such correlations have not been studied among child and adolescent patients with AD, but some studies in other disease areas have reported good/excellent correlations between child-reported QoL and caregiver-proxy reports (e.g., in patients with acne [ 15 ], juvenile fibromyalgia syndrome [ 16 ], or epilepsy [ 17 ]), while others have reported poor/moderate agreements (e.g., in patients with asthma [ 18 , 19 ] or impaired mobility [ 20 ]). It has also been suggested that caregivers are better at judging physical rather than psychological or emotional aspects of QoL [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…An existing IRB-approved longitudinal patient registry for the purposes of clinical research was used to identify patients with disordered eating. Details regarding this patient registry were previously published by Gmuca et al [23]. Given this study was a retrospective chart review and patients were not screened for disordered eating, we a priori identified clinical variables and patient reported information to determine the presence of disordered eating.…”
Section: Methodsmentioning
confidence: 99%